Large improvement of RF transmission efficiency and reception sensitivity for human in vivo (31)P MRS imaging using ultrahigh dielectric constant materials at 7 T - Lee, Byeong-Yeul (Magn Reson Imaging, 2017)
In vivo(31)P MRS provides a unique and important imaging tool for studying high-energy phosphate metabolism and bioenergetics noninvasively. However, compared to (1)H MRS, (31)P MRS with a relatively low gyromagnetic ratio (γ) has a lower and limited sensitivity even at ultrahigh field. The proof of concept has been recently demonstrated that the use of high dielectric constant (HDC) materials between RF coil and object sample could increase MRI signal and reduce required RF transmission power for reaching the same RF pulse flip angle in the region of interest. For low-γ MRS applications operated at relatively lower frequency, however, it demands the dielectric materials with a much higher permittivity for achieving optimal performance. We conducted a (31)P MRS imaging study using ultra-HDC (uHDC; with a relative permittivity of ~1200) material blocks incorporated with an RF volume coil at ultrahigh field of 7.0 T. The experimental results from phantom and human calf muscle demonstrate that the uHDC technique significantly enhanced RF magnetic transmit field ( [Formula: see text]) and reception field ( [Formula: see text]) and the gain could reach up to two folds in the tissue near the uHDC blocks. The overall results indicate that the incorporation of the uHDC materials having an appropriate permittivity value with a RF coil can significantly increase detection sensitivity and reduces RF transmission power for X-nuclei MRS applications at ultrahigh field. The uHDC technology could provide an efficient, cost-effective engineering solution for achieving high detection sensitivity and concurrently minimizing tissue heating concern for human MRS and MRI applications.